A STUDY ON IMPLEMENTATION OF MGNREGA SCHEME ON POVERTY ELEVATION IN RURAL POPULATION ACROSS THE STATES IN INDIA. - N. Arunsankar; R K Prema (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is known for Agrarian economy and two third of the population residing in rural areas. Around 30% of the contribution to Indian GDP come s from Rural India and the national income contribution from rural area is 46%. Developing countries like India possess competitive advantage in producing agricultural products and thereby ranks top in Primary sector. Rural Indian labors, a higher proportion is involved in agriculture. A report by CMIE, 2021 states that the metrics shows a big improvement in the labor participation rate, and the concentration is by rural India. Rural India contributes a very concrete support in our country growth. In order to get balance in the increased population, higher proportion of the people need to put in work. For that the country must be in a position to offer employment opportunity to all, who demand for it. One such useful scheme is Mahatma Gandhi National Rural Employment Guarantee Act (MGNREA) which guarantees 100 days of wage employment in a financial year to a rural household whose adult member volunteers to do unskilled manual wok. If the government fails to provide employment for a registered rural adult, under this scheme government is liable to pay unemployment allowance.